On Ballast, Sleepers and Rails: Hard Immobility at the Service of Soft Mobility. For a Semiotics of Materiality - Bertrand , Denis (E|C, 2023)
Because of its low ecological impact, the train is a favoured means of mobility. We focus on the materials that justify this. This technical field calls for some introductory definitions and opens up the general problem: the semiotics of the sensible and the figurative paths of meaning. After tracing the theoretical history of this field and highlighting its topicality, we focus on the substance of expression: the materiality of the objects from which we draw meaning. We then move on to the study of the mineral world (ballast), woody matter (sleepers) and the metallic world (rails), from both a paradigmatic and syntagmatic point of view. We’ll be looking at how these expressive substances harbour, in their materiality, a universe of content: what forces are they subject to? What tensions and resistances determine their form of existence? What are the paths of matter that drive them? To conclude, what is at stake in a tribological semiotics of materiality.